2013
DOI: 10.1115/1.4023435
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Thermal Performance and Energy Conservation Potential of Hybrid Earth Air Tunnel Heat Exchanger in Hot and Dry Climate—In Situ Measurement

Abstract: Earth air tunnel heat exchanger is a passive cooling device with advantageous feature to reduce energy consumption in buildings. Curtailing the electricity consumption of conventional vapor compression system based air-conditioner is a major concern especially in area with hot and dry weather conditions. The performance of conventional air-conditioners can substantially be enhanced by coupling these active cooling systems with passive cooling systems. In the present research, the thermal performance and energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…It is observed from Fig. 11 (Misra et al 2013) the experimental results with the variation of 0.8-7.93 %. This error may occur due to the improper insulation of pipes, variation in coefficient of friction of materials used in the simulation, and irregularities, such as fitting and joints in the experimental setup.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…It is observed from Fig. 11 (Misra et al 2013) the experimental results with the variation of 0.8-7.93 %. This error may occur due to the improper insulation of pipes, variation in coefficient of friction of materials used in the simulation, and irregularities, such as fitting and joints in the experimental setup.…”
Section: Resultsmentioning
confidence: 82%
“…Some researchers have done work using EATHE for air conditioning. One of the experimental studies was performed on the hybrid EATHE (Misra et al 2013) for the conditions of Ajmer (India). In their experimental analysis, they used the thermal and physical parameters of various materials, such as soil density, soil thermal conductivity, soil specific heat, and pipe thermal conductivity as 2050 kg/m 3 , 0.52 W/mK, 1.840 kJ/kg K, and 0.16 W/mK, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the recent years, scope of EAHE systems is being investigated in developing countries also. Many researchers adopted EAHE system alone or in combination with solar chimney, conventional heating ventilation and air conditioning (HVAC) system, phase changing material (PCM) and other renewable technologies, using experimental, modeling or both methodologies for their research works [25][26][27].…”
Section: Eahe Systems Studiesmentioning
confidence: 99%
“…A study done by Orme has suggested that the energy consumption by HVAC systems in the residential building is nearly about 68% of the total consumption [20], which can be reduced significantly. Researches have been done to maintain [21,22] and improve [23][24][25] the thermal environment of buildings along with increasing its energy saving potential. However, one of the best passive approaches for reaching these target reductions in energy consumption in HVAC systems is to utilize increased natural ventilation, which would lead to an exchange of air with the outside surroundings and would also lead to the circulation of air within the building, without the help of any mechanical systems.…”
Section: Introductionmentioning
confidence: 99%